Analisis Pertumbuhan Pembibitan Pueraria javanica pada Komposisi Media Seresah dalam Ketiak Pelepah pada Batang Kelapa Sawit - Danie Indra Yama (JURNAL CITRA WIDYA EDUKASI, 2019)
The purpose of this research is to know the influence of growth media of organic material on palm oil stem response of Pueraria javanica in nursery, to get the composition of growth media of organic material on palm oil stem for nursery Pueraria javanica. The research was conducted for 5 months in the Green House and the Biological Laboratory of Politeknik Kelapa Sawit Citra Widya Edukasi, Bekasi using Randomized Complete Block Design with three replicates and three samples with treatment A1: 100% organic matter, A2: Subsoil 100%, A3: 40% organic matter + 60 % sub soil, A4: 60% organic matter + 40% sub soil, A5: 80% organic matter + 20% sub soil. The data were analyzed by analysis of variance (ANOVA), if there is significant treatment effect the further was analyzed by Duncan Multiple Range Test 5%, the parameters were leaf area, leaf area ratio, leaf specific weight, leaf mass density, stem density, root mass density, root-shoot ratio. The results showed that the growth media of organic material on palm oil stem was influential in increasing leaf area and density of the organelles in the leaves although Pueraria javanica can grow well on various media, the composition of 40% organic mater + 60 % sub soil suitable for nursery Pueraria javanica in increasing leaf area but the media with composition 100% organic matter take effect of of leaf thickness.